Lily's promise - Erskine, Kathryn (Quill Tree Books, an imprint of HarperCollinsPublishers, 2021)
"Lily made her dad an important promise before he passed away; that she would...speak her mind at least five times. But speaking up one time, let alone five, is easier said than done. It'll be even harder now that Lily must attend public school for the first time. Fortunately, she meets curling-obsessed Hobart and quiet Dunya at the beginning of sixth grade...But when Lily and her friends are bullied by Ryan and his mean clique, she quickly discovers the true meaning of friendship and speaking out"--